(untitled) (The Research of Medical Science Review, 2025)
Background: Knee osteoarthritis (OA) is a degenerative joint disease commonly affecting middle-aged and older adults, leading to pain and functional decline. Pain perception is a significant factor in the progression of functional impairment in knee OA patients. This study aimed to explore the relationship between pain perception and functional decline in individuals with knee OA. Methods: A cross-sectional study was conducted with 120 participants diagnosed with knee OA. Pain perception was assessed using the Visual Analog Scale (VAS) and the Short Form McGill Pain Questionnaire (SF-MPQ). Functional decline was measured through the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Timed Up and Go Test (TUG), and 6-Minute Walk Test (6MWT). Psychological factors were evaluated using the Hospital Anxiety and Depression Scale (HADS). Data were analyzed using correlation and regression analyses. Results: The study found significant positive correlations between pain perception (VAS) and functional decline, including mobility and endurance measures (TUG and 6MWT) (r = 0.55–0.63, p < 0.001). Anxiety, as measured by HADS, was also associated with functional outcomes (r = 0.45, p = 0.002). Multiple regression analysis revealed that pain perception, anxiety, and BMI were significant predictors of functional decline. Females and older adults reported higher pain levels and worse functional performance compared to males and younger adults. Conclusion: Pain perception significantly impacts functional decline in knee OA patients. Psychological factors and demographic characteristics, such as gender and age, further contribute to functional impairment. These findings highlight the need for multidisciplinary interventions addressing pain, mental health, and lifestyle factors in managing knee OA. Future research should explore long-term interventions to improve patient outcomes.